Pengembangan Kegiatan Inovatif Ramah Lingkungan di Calon Sekolah Adiwiyata Wilayah Kabupaten Semarang - Ngabekti, Sri; Widiyaningrum, Priyantini; Lisdiana, Lisdiana; Kartijono, Nugroho Edi; Purwantoyo, Eling; Haris, Amnan (Universitas Negeri Semarang, 2024)
Adiwiyata School is a program emphasizing the community's concern for environmental preservation. This activity aims to develop environmentally friendly innovative activities by the school's potential, integrate environmentally friendly innovative activities in the RPP, and implement innovative activities to produce environmentally friendly products. Methods for implementing activities include (1) Discussion and practice methods for making leaf bone crafts from waste and ecoprint; (2) Preparation of CP, ATP, and teaching modules to implement innovative activities according to the Merdeka Curriculum; (3) Opinion poll questionnaire to determine participants' responses regarding activities that have been and will be implemented. The activity was carried out on Wednesday, July 26, 2023, with independent practice assignment at school for 2 weeks and evaluation monitoring at school on Thursday, September 14, 2023. The results of the activity showed that (1) As many as 90% of the school community had carried out innovative activity practices and developed teaching modules that integrate innovative activities with an independent curriculum format, (2) the school has succeeded in making environmentally friendly innovative products in the form of: leaf crafts, ecoprints, aromatherapy candles by utilizing waste cooking oil (used cooking oil) and recycling plastic, cloth, wood, and other waste, (3) The results of the poll questionnaire received very good responses. Based on the results of the activity, it can be explained that the activity targets can be achieved well. The activeness of the participants who attended on average reached 100%. Participants' activeness in practicing and compiling teaching modules integrating innovative environmentally friendly activities reached 90%.